PERANCANGAN SISTEM INFORMASI BIAYA PEMESANAN BARANG MENGUNAKAN METODE ACTIVITY BASED COSTING BERBASIS WEB (STUDI KASUS : PT. ISS INDONESIA) - Mawandi Kusuma (CV. Multi Kreasi Media, 2024)
Technological developments that are developing rapidly at this time are very good when problems within the company use it to overcome problems related to improving the quality of the company in providing services. In overcoming problems related to ordering goods within a company so that it is orderly and fast, it is necessary to have a system that is provided to help employees and companies to be able to order and calculate the expenditure of goods properly. The designed information system is a web-based system with a database for data management and an information system developed using the PHP programming language, so that it can help employees and companies to use it. The information system developed uses the Activity Based Costing (ABC) method. Activity Based Costing method is a cost accounting method that is intended to produce cost information by activity that is useful for management. In the development of this information system there is a design analysis that is used, namely Context Diagrams, Data Flow Diagrams, Entity Relationship Diagrams and Flowcharts. In this information system, employees will place an order for the equipment to be used and the company management will receive the request through the goods ordering information system. After placing an order for goods and equipment, the system will automatically calculate expenses and manage order data in the goods ordering information system.